Massive Perivillous Fibrin Deposition and Chronic Histiocytic Intervillositis a Complication of SARS-CoV-2 Infection. (September 2021) - Marton, T; Hargitai, B; Hunter, K; Pugh, M; Murray, P
An emerging complication of COVID-19 (SARS-CoV-2) infection is reported. A 23-year-old patient presented with high temperature and reduced fetal movements at 25 + 5/40 weeks of gestation. RT-PCR proved maternal COVID-19 infection. Ultrasound examination confirmed intrauterine death. Placenta histology showed necrosis of the villous trophoblast, associated with Chronic Histiocytic Intervillositis (CHI) and Massive Perivillous Fibrin Deposition (MPFD) with up to 90% - of the intervillous spaces being involved. Immunohistochemistry showed CD68 positive histiocytes in the intervillous spaces and the villous trophoblast was positive for the COVID-19 spike protein. RNA scope signal was indicative of the presence of the viral genome and active viral replication in the villous trophoblastic cells, respectively. MPFD is a gradually developing end-stage disease with various etiology, including autoimmune and alloimmune maternal response to antigens expressed at the feto-maternal interface and frequently accompanies chronic alloimmune villitis or histiocytic intervillositis. Covid-19 infection is associated with similar pattern of histological changes of the placenta leading to placental insufficiency and fetal death. This case report supports maternal- fetal vertical transmission of SARS-CoV-2 virus leading to placental insufficiency and fetal demise. MPFD and CHI appear to be the typical placental histology for SARS-CoV-2 virus infection associated fetal demise.